Novel approaches of geotechnical investigation for mine closure projects in Canada - Deamude, D; Naeini, AA; Lee, C-E (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Innovative data acquisition and ground monitoring approaches are now being used to support the decommissioning and reclamation of the various types of excavations found at mine sites. Remote data acquisition and visualization technologies have improved the ability to gain a spatial understanding of mine excavations and structures as well as the quality of the surrounding rock mass. These technologies have led to greater confidence and reliability in the outcome of mine closure designs by enabling advanced engineering analyses and increasing personnel safety. To ensure the safety of the public and allow for productive use of the land after the mine is closed, geotechnical assessments are conducted to evaluate the longer-term stability of open pit and underground mine excavations. The acquisition of data to support these studies can be challenging particularly for historic or legacy mine sites where there is limited availability of design and implementation records and inspection reports on the state of excavations post mining. These excavations can also be difficult to access safely because of rock mass damage caused by instability surrounding these structures. The installation of ground monitoring methods can also be challenging due to the instability that occurs post-mining. The technologies and monitoring methods discussed in this paper include photogrammetry, slope inclinometers (SI), time domain reflectometry (TDR), bathymetric and sonar surveys, terrestrial, Light Detection and Ranging (LiDAR), and Interferometric Synthetic Aperture Radar (InSAR). Example uses of these technologies and surveying methods in various mine closure projects are reviewed including advantages and limitations of each technique mentioned above. Assessing the usage and execution of these techniques can determine which methods are appropriate for use in other projects.